Divine action and modern science - Saunders, Nicholas, 1974- (Cambridge University Press, 2002)
Divine Action and Modern Science considers the relationship between the natural sciences and the concept of God acting in the world. The book concludes that we are still far from a satisfactory account of how God might act in a manner that is consonant with modern science.